Outcomes of 270 Consecutive Deep Inferior Epigastric Perforator Flaps for Breast Reconstruction. (June 2018) - Zhang, Angie; Dayicioglu, Deniz
Abstract : Background: The deep inferior epigastric perforator (DIEP) flap has gradually become the superior choice for autologous breast reconstruction because it reduces donor site morbidity, abdominal wall complications, and postoperative recovery time when compared with other flap types. Methods: The purposes of this study are to report on the experience and clinical outcomes of consecutive DIEP flap breast reconstructions performed by a single surgeon at a cancer center between April 2011 and May 2016 and to characterize the trends among these flaps. Results: Two hundred seventy DIEP flaps from 202 consecutive patients were assessed. Patient ages ranged from 31 to 73 years, with a mean (SD) of 52.81 (9.89) years. Ischemia time ranged from 17 to 211 minutes (mean [SD], 51.51 [23.02] minutes), and procedure length (including mastectomy time) was between 224 and 950 minutes (mean [SD], 548.13 [154.77] minutes). Venous coupler size was between 2 and 4 mm (mean [SD], 2.69 [0.33] mm), and 1 to 3 perforating vessels were maintained per flap (mean [SD], 1.71 [0.68] perforators). Total reexploration rate was 3.3% (n = 9), and the total complete flap loss rate was 1.1% (n = 3). Conclusions: In our experience, the DIEP flap is a safe, consistent, and reliable option for breast reconstruction.